2019
DOI: 10.1126/scitranslmed.aav3113
|View full text |Cite
|
Sign up to set email alerts
|

A virus-like particle vaccine prevents equine encephalitis virus infection in nonhuman primates

Abstract: Western, Eastern, and Venezuelan equine encephalitis viruses (WEEV, EEEV, and VEEV, respectively) are important mosquito-borne agents that pose public health and bioterrorism threats. Despite considerable advances in understanding alphavirus replication, there are currently no available effective vaccines or antiviral treatments against these highly lethal pathogens. To develop a potential countermeasure for viral encephalitis, we generated a trivalent, or three-component, EEV vaccine composed of virus-like pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
43
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 52 publications
3
43
2
Order By: Relevance
“…particle representing a single alphavirus, neutralizing antibodies developed only to the corresponding virus with no cross-reactive neutralization observed (Ko et al, 2019). Both the E1 and E2 envelope protein sequences of EEEV differ significantly from the other encephalitic alphaviruses with only 49% and 58% sequence homology in the E1 protein, and 44% and 46% sequence homology in the E2 protein compared to WEEV and VEEV, respectively (Hahn et al, 1988).…”
Section: Discussionmentioning
confidence: 98%
“…particle representing a single alphavirus, neutralizing antibodies developed only to the corresponding virus with no cross-reactive neutralization observed (Ko et al, 2019). Both the E1 and E2 envelope protein sequences of EEEV differ significantly from the other encephalitic alphaviruses with only 49% and 58% sequence homology in the E1 protein, and 44% and 46% sequence homology in the E2 protein compared to WEEV and VEEV, respectively (Hahn et al, 1988).…”
Section: Discussionmentioning
confidence: 98%
“…Anti-WEEV immune serum from rabbits [ 23 ], mice [ 14 ] and NHPs [ 25 ] passively administered to mice can protect against lethal WEE disease. However, to date, no neutralizing or protective murine, human or human-like anti-WEEV monoclonal antibodies have been identified [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In vaccination studies delivering WEEV, EEEV and VEEV antigen concomitantly, WEEV antigens appear to be less immunogenic in comparison to VEEV and EEEV antigens. This is evidenced by lower neutralizing and binding antibody titers to WEEV vaccine components when similar protein concentrations are delivered in a trivalent formulation [ 25 , 31 ]. Alternatively, the reduced immunogenicity of WEEV antigen in these studies may be a result of immunologic interference similar to what was observed in humans after sequential alphavirus vaccine administration [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The last recorded human cases of WEEV were in 2009 in Uruguay (10), and virus is rarely detected in mosquito pools (11). A trivalent alphavirus virus-like particle vaccine was recently developed (12) and is undergoing human safety testing. Due to the rarity of WEEV cases, the McMillan strain (GenBank accession number GQ287640) is the only complete human isolate sequence available.…”
mentioning
confidence: 99%